METODE ROLEPLAY DALAM MENINGKATKAN KEMAMPUAN PENGGUNAAN SONKEIGO DAN KENJOUGO (Studi Kasus Pada Mahasiswa Angkatan 2017 Program Studi Pendidikan Bahasa Jepang FKIP Universitas Riau) - Srie Indah Wellyawati; Mangatur Sinaga; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study describes and explains the application of the Roleplay method in learning sonkeigo and kenjougo in Japanese language education students at FKIP Riau University. The purpose of this study was to determine whether the Roleplay method was effective in improving sonkeigo and kenjougo learning in Japanese language education students of FKIP Riau University after using the Roleplay method. In this study the authors used a quasi-experimental research design characterized by a comparison class. Data collection was carried out using test techniques. The test results were processed using the Kolmogorov-Smirnova test in SPSS Version 16. The test results in the pretest and posttest of the experimental class had increased, in the pretest the average value of students was 78.7 while in the posttest 93.1. Thus, the Roleplay method is effective in improving the learning outcomes of Japanese Language Education FKIP Riau University students in 2017.Key Words: Roleplay Method, Sonkeigo, Kenjougo